2005
DOI: 10.1093/toxsci/kfi146
|View full text |Cite
|
Sign up to set email alerts
|

Ribotoxic Stress Response to the Trichothecene Deoxynivalenol in the Macrophage Involves the Src Family Kinase Hck

Abstract: Trichothecene mycotoxins and other translational inhibitors activate mitogen-activated protein kinase (MAPKs) by a mechanism called the "ribotoxic stress response," which drives both cytokine gene expression and apoptosis in macrophages. The purpose of this study was to identify upstream kinases involved in the ribotoxic stress response using the trichothecene deoxynivalenol (DON) and the RAW 264.7 macrophage as models. DON (100 to 1000 ng/ml) dose-dependently induced phosphorylation of c-Jun N-terminal protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 69 publications
6
68
0
Order By: Relevance
“…Trichothecenes have immunoregulatory and cytotoxic effects on immune cells (28, 36, 49 -52). In addition, it has been concluded that these mycotoxins cause MAPK-mediated ribotoxic stress and apoptosis (53)(54)(55). We have previously shown in a mouse model of asthma that exposure to toxic S. chartarum induces lung inflammation characterized by the infiltration of immune cells, as well as the formation of granulomas and giant cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…Trichothecenes have immunoregulatory and cytotoxic effects on immune cells (28, 36, 49 -52). In addition, it has been concluded that these mycotoxins cause MAPK-mediated ribotoxic stress and apoptosis (53)(54)(55). We have previously shown in a mouse model of asthma that exposure to toxic S. chartarum induces lung inflammation characterized by the infiltration of immune cells, as well as the formation of granulomas and giant cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…ERK1/2, a MAPK, is activated both by trichothecenes such as DON via a process termed the 'ribotoxic stress response' and by the invasion of Salmonella Typhimurium in macrophages [29,39]. Recently, Yang et al [37] described that DON induces p21 mRNA stability in human epithelial cells in terms of interactions RNA-binding proteins via ERK 1/2 activation.…”
Section: Don Induced Cell Morphology Changesmentioning
confidence: 99%
“…However, many of their toxic effects might also be related to a rapidly ensuing dysregulation of intracellular cell signaling and consequent alterations in downstream gene expression [27]. Exposure to low levels of trichothecenes appears to promote expression of a diverse array of cytokines and proinflammatory genes in vitro and in vivo via a mechanism known as the ribotoxic stress response that involves multiple intracellular signaling cascades [26,38,39]. Trichothecenes such as DON are also known to rapidly activate mitogen-activated protein kinase (MAPK) via a process termed the ''ribotoxic stress response''.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the toxin functions as an anti-apoptotic agent by increasing the survival of MCF-7 cell cultures undergoing apoptosis caused by serum withdrawal. On the other hand, the ribotoxic DON was found capable of inducing competing apoptotic (p38/p53/Bax/mitochondria/ caspase-3) and survival (ERK/AKT/p90Rsk/Bad) signaling pathways in macrophages (Zhou et al 2005). Because of their mode of action, microRNAs (miRNAs or miRs), members of the RNA interference (RNAi) system, seem particularly suitable for studying the molecular processes underlying pathological alterations of cells and tissues at the gene and protein levels (Hudder and Novak 2008).…”
Section: Introductionmentioning
confidence: 99%